2011
DOI: 10.1002/jwmg.160
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with use of wildlife underpasses and importance of long‐term monitoring

Abstract: We evaluated use of 6 wildlife underpasses (UP) using video camera surveillance along State Route 260 in Arizona, USA. We documented wildlife use and compared successful UP crossings by various species and among UP. From 2002 to 2008, we recorded visits by 15,134 animals of 21 species (16 wildlife, 5 domestic) resulting in 72.4% crossing through UP. Elk (Cervus elaphus) accounted for 68% of recorded animals, white-tailed deer (Odocoileus virginianus) and mule deer (O. hemionus) accounted for 13% and 6%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 25 publications
(54 reference statements)
4
56
0
Order By: Relevance
“…These results are consistent with theoretical models that consider how animal body size, movement speed, traffic volume and road width influence DVC (Van Langevelde and Jaarsma 2004). Mitigation measures along roads characterized by high traffic volume should therefore focus on deterring wildlife access to the road surface, i.e., with exclusion fencing (Clevenger et al 2001, Olsson and Widen 2008, McCollister and Van Manen 2010, Gagnon et al 2011.…”
Section: Discussionsupporting
confidence: 76%
“…These results are consistent with theoretical models that consider how animal body size, movement speed, traffic volume and road width influence DVC (Van Langevelde and Jaarsma 2004). Mitigation measures along roads characterized by high traffic volume should therefore focus on deterring wildlife access to the road surface, i.e., with exclusion fencing (Clevenger et al 2001, Olsson and Widen 2008, McCollister and Van Manen 2010, Gagnon et al 2011.…”
Section: Discussionsupporting
confidence: 76%
“…Gagnon et al (2011) found that elks (Cervus elaphus) adapted and habituated to terrestrial crossing structures over years, and some factors, such as season, time of the day and length of monitoring, that influenced the crossing frequencies in the first year of monitoring, became insignificant after four years. Given the remarkably quick habituation shown by our study species, we may be able to identify the factors influencing their long term crossing behaviours even in less than four years.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, animals have been observed to show reluctance towards wildlife crossing structures for a certain period of time before they habituated to them and started using them regularly (Gagnon et al 2011). For example, possums and gliders in eastern Australia started using rope bridges after 7 to 17 months of bridge constructions, and the number of crossings increased over time until it reached asymptotes (Weston et al 2011, Goldingay et al 2013, Soanes et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, many studies were in agreement that the effectiveness of crossing structures, fencing, deterrents, and traffic calming measures, was species-specific [96,98,105,121]. A generic "one-size fits all" crossing structure or deterrent does not exist.…”
Section: Survey Design and Mitigationmentioning
confidence: 95%
“…Overall, many studies agreed that crossing structures alone where not as effective as expected [98][99][100][101][102], and those studies that reported road mortality rates more often saw reductions ranging from 10 to 20% [103,104]. Nevertheless, two studies speculated that crossing structures were still biologically effective as low crossing frequencies may be enough to maintain functional connectivity [105,106].…”
Section: Survey Design and Mitigationmentioning
confidence: 97%